LP340, a novel histone deacetylase inhibitor, decreases liver injury and fibrosis in mice: role of oxidative stress and microRNA-23a - Samuvel, Devadoss J.; Lemasters, John J.; Chou, C. James; Zhong, Zhi (Frontiers in Pharmacology, 2024)
Effective therapy for liver fibrosis is lacking. Here, we examined whether LP340, the lead candidate of a new-generation of hydrazide-based HDAC1,2,3 inhibitors (HDACi), decreases liver fibrosis. Liver fibrosis was induced by CCl4 treatment and bile duct ligation (BDL) in mice. At 6 weeks (wk) after CCl4, serum alanine aminotransferase increased, and necrotic cell death and leukocyte infiltration occurred in the liver. Tumor necrosis factor- and myeloperoxidase markedly increased, indicating inflammation. After 6 wk, αsmooth muscle actin (αSMA) and collagen-1 expression increased by 80% and 575%, respectively, indicating hepatic stellate cell (HSC) activation and fibrogenesis. Fibrosis detected by trichrome and Sirius-red staining occurred primarily in pericentral regions with some bridging fibrosis in liver sections. 4-Hydroxynonenal adducts (indicator of oxidative stress), the profibrotic cytokine transforming growth factor-β (TGFβ), and TGFβ downstream signaling molecules phospho-Smad2/3 also markedly increased. LP340 attenuated indices of liver injury, inflammation, and fibrosis markedly. Moreover, Skirelated novel protein-N (SnoN), an endogenous inhibitor of TGFβ signaling, decreased, whereas SnoN expression suppressor microRNA-23a (miR23a) increased markedly. LP340 (0.05 mg/kg, ig., daily during the last 2 wk of CCl4 treatment) decreased 4hydroxynonenal adducts and miR23a production, blunted SnoN decreases, and inhibited the TGFβ/Smad signaling. By contrast, LP340 had no effect on matrix metalloproteinase-9 expression. LP340 increased histone-3 acetylation but not tubulin acetylation, indicating that LP340 inhibited Class-I but not Class-II HDAC in vivo. After BDL, focal necrosis, inflammation, ductular reactions, and portal and bridging fibrosis occurred at 2 wk, and αSMA and collagen-1 expression increased by 256% and 560%, respectively. LP340 attenuated liver injury, ductular reactions, inflammation, and liver fibrosis. LP340 also decreased 4-hydroxynonenal adducts and miR23a production, prevented SnoN decreases, and inhibited the TGFβ/Smad signaling after BDL. In vitro, LP340 inhibited immortal human hepatic stellate cells (hTERT-HSC) activation in culture (αSMA and collagen-1 expression) as well as miR23a production, demonstrating its direct inhibitory effects on HSC. In conclusions, LP340 is a promising therapy for both portal and pericentral liver fibrosis, and it works by inhibiting oxidative stress and decreasing miR23a.